2009
DOI: 10.1097/sap.0b013e31819516cc
|View full text |Cite
|
Sign up to set email alerts
|

Single Stage Reconstruction of Ruptured Tendoachilles Tendon With Skin Cover Using Distally Based Superficial Sural Artery Flap

Abstract: Ruptured tendoachilles along with skin defect is a complex problem to reconstruct. Both things require a priority. Single stage reconstruction of ruptured tendoachilles tendon with skin cover using distally based superficial sural arterial flap allows us to perform both. This procedure gives excellent result, shortens the stay, thereby reducing the cost. This method is a simple solution to the complex problem like ruptured tendoachilles with skin defect. In this study, 6 patients with rupture of tendoachilles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
0
12
0
1
Order By: Relevance
“…Five out of six patients needed a small size split thickness skin graft at the donor site after a mean time of 7.1 days (range 7-9) of vacuum therapy to improve the granulation tissue and reduce the cosmetic impact on the forearm. DASH score values relating to the donor extremity resulted with a mean value of 8.0 points (range [3][4][5][6][7][8][9][10][11][12][13][14][15] with no significant functional impairment complained by patients. The MRI study at 8 months FU showed a nearly normal shape of the reconstructed tendon without interruptions, and the fusion between the two segments of FCR reaching in size the original Achilles tendon (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five out of six patients needed a small size split thickness skin graft at the donor site after a mean time of 7.1 days (range 7-9) of vacuum therapy to improve the granulation tissue and reduce the cosmetic impact on the forearm. DASH score values relating to the donor extremity resulted with a mean value of 8.0 points (range [3][4][5][6][7][8][9][10][11][12][13][14][15] with no significant functional impairment complained by patients. The MRI study at 8 months FU showed a nearly normal shape of the reconstructed tendon without interruptions, and the fusion between the two segments of FCR reaching in size the original Achilles tendon (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A composite vascularized flap, able to provide healthy tissues to simultaneously reconstruct both tendon and skin, may be a logical alternative. Several donor sites able to offer vascularized skin and tendon are available, and different flaps have been addressed in literature …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the distally based peroneus brevis muscle flap (PBF) was first reported by Donski and Fodgestan [16] , it became more popular when Masquelet described the surgical procedure in detail based on of his anatomical findings [17] and by Lyle and Colborn [18] . In our clinical routine it has been implemented as a workhorse for reconstructing small full thickness defects in the distal lower leg, ankle and heel [19][20][21][22][23][24] . Later papers added their experiences and highlighted the key points that need to be taken into account McHenry et al [25] and Eren et al [26] .…”
Section: Introductionmentioning
confidence: 99%